To find the value of \( x \), we start by noting the relationships among the angles described in the problem.
-
Given Angles:
- \( \angle C-G-E = 90^\circ \)
- \( \angle C-G-A = 51^\circ \) (given)
- \( \angle D-G-B = 51^\circ \) (vertically opposite to angle \( \angle C-G-A \))
-
Calculate \( \angle A-G-E \):
- Since \( \angle C-G-E = \angle C-G-A + \angle A-G-E \): \[ 90^\circ = 51^\circ + \angle A-G-E \] \[ \angle A-G-E = 90^\circ - 51^\circ = 39^\circ \]
-
Relationship with \( x \):
- Since \( \angle A-G-E \) (39°) is vertically opposite to \( \angle B-G-F \) (which is marked as \( x \)): \[ \angle B-G-F = 39^\circ \]
Thus, the value of \( x \) is 39°.
The answer is therefore: 39 °